Chlorination disinfection by-products in municipal drinking water – A review. (10th November 2020) - Mazhar, Mohd Aamir; Khan, Nadeem A.; Ahmed, Sirajuddin; Khan, Afzal Husain; Hussain, Azhar; Rahisuddin,; Changani, Fazlollah; Yousefi, Mahmood; Ahmadi, Shahin; Vambol, Viola
Abstract: For long time water disinfection is being done to inactivate or control bacteria populations in the treated water and simple chlorination is the most common method to disinfect the water. Almost certainly for over a decade chlorination is being effectively utilized for controlling of water borne contamination. An assortment of disinfection by-products (DBPs) are formed like trihalomethanes (THMs), haloacetic acids (HAAs) and halogenated acetonitriles (HANs) etc., when the naturally occurring natural organic matters (NOMs) present in raw water reacts with chlorine that may have adverse health impacts on humans. These compounds fall apart the water quality and there are epidemiological confirmations of close connection between its emergence and unfavourable results especially the malignant growths of fundamental organs in individuals. Concerns related with the prospective health hazards of DBPs provoked a few industrialized nations to build up various guidelines. Due to lack of data more research is required to understand its adverse health effects on human beings which are being restrained by funds required for researches. DPBs dermal and inhalation exposure routes have greater risk as compared to ingestion route. The DBPs can be controlled by methods like coagulation with polymer, alum, lime or iron, sulphates, adsorption on activated carbons, ion exchange or membrane process and to more effectively reduce the precursor i.e. NOMs. In this paper we have discussed about the formation of disinfection by-products in treated municipal water during chlorination and how these DBPs were discovered. Moreover, we briefly compared the present status of their guidelines value or regulations in India with other regulating bodies and what are the category of cancer groups under which the different DBPs are categorized by WHO. A portion of the basic science related to DBPs formation is explained and the different exposure routes of DBPs in a human body are discussed. Fifty-two studies were reviewed about DBPs toxicity and epidemiology to understand the greatness of hazards caused by exposure of DBPs as shown by various researchers. Many innovations and methodologies can be used for controlling or removal of the DBPs. Highlights: Chlorine is the principal disinfectant used worldwide with more benefit when compared with the other disinfectants present. Disinfection by-products are carcinogenic but can be removed by various techniques. Microbial risk is of greater magnitude, then the risk presented by disinfection byproducts.